Features of anxiety in university students and features of correction by art-therapy - Jung, N.; Isaeva, T.; Vishtalenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article discusses the features of the manifestation of anxiety in university students and provides the main mechanisms for the correction of anxiety using art therapy. In the system of modern scientific knowledge, the phenomenon of anxiety and its impact on human development and its adaptation to the environment is one of the main issues of biology, medicine, pedagogy, and psychology. The article emphasizes the features of personality formation in adolescence, describes the main psychological mechanisms of the development of the emotional sphere. An analysis of the psychological and pedagogical literature on the use of the art therapy method as a means of correcting adolescents' anxiety levels has been performed. The results of studying the peculiarities of anxiety in university students are demonstrated. Left-handed children were found to be more anxious than right-handed. Thus, the article presents the results of a study that was carried out using a complex of appropriate psychodiagnostic techniques. The students of higher educational institutions took part in it. The article identifies the level of anxiety in the group and major differences among the subjects. It is revealed that the dynamics of the psychoemotional state is affected by the peculiarity of the left and right hemisphere asymmetries. However, with hereditary left-handedness, left-handed people are more neurotic, unlike right-handed people. It was confirmed that Art therapy, as a method of psychological and pedagogical correction, is the most effective means of psychocorrectional influence on the emotional sphere of a person. It has been determined that art therapy helps a person solve internal conflicts, deal with strong emotions, and helps to realize his feelings.
Keywords: study; interhemispheric asymmetry; hemisphere; anxiety; students; young age; the personality of a student; adaptation